2019
DOI: 10.1111/jasp.12570
|View full text |Cite
|
Sign up to set email alerts
|

Stigma as framed onYouTube: Effects of personal experiences videos on students’ beliefs about medicalizing intersex

Abstract: People with physical intersex characteristics can be subject to medical interventions that risk human rights to bodily integrity and self‐determination. Proponents and opponents of medicalization use personal narrative videos on YouTube to frame intersex as a stigma best understood through a medical or social identity frame. Ninety‐nine psychology students watched one of two YouTube videos with either a medical or social identity frame, or participated in a comparison group who watched no video. Participants e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Tee and Hegarty (2006) developed a measure of belief in two and only two genders that are defined by sex characteristics. Two recent studies found gender binary beliefs to predict support for genital surgery on intersex characteristics (Hegarty et al, , 2019. We expected to replicate those findings here.…”
Section: The Present Studysupporting
confidence: 81%
See 2 more Smart Citations
“…Tee and Hegarty (2006) developed a measure of belief in two and only two genders that are defined by sex characteristics. Two recent studies found gender binary beliefs to predict support for genital surgery on intersex characteristics (Hegarty et al, , 2019. We expected to replicate those findings here.…”
Section: The Present Studysupporting
confidence: 81%
“…In one, belief in the authority of medicine predicted greater support for surgery on children who were labelled 'intersex' rather than 'female' (Smith & Hegarty, 2020). In another, openness to influence by first-person narratives of intersex people was predicted by opposition to the gender binary (Hegarty et al, 2019). If this interpretation is correct, then lay people's capacity to think about intersex in more than one frame of reference may have some clinical implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having more knowledge of the diverse understandings that patients might bring to consultations puts health professionals in a better position to empower patients and their families to fully participate in decision-making in uncertain situations about unfamiliar topics. The present study bridges the gap between experiments showing how framing affects sense making (e.g., Hegarty, Smith, & Bogan-Carey, 2019;Streuli et al, 2013) and studies highlighting the sense making needs that parents report retrospectively after medical decisions have been made (e.g., Sanders et al, 2008).…”
Section: Addressing Underpinning Understandings In Clinical Practicementioning
confidence: 66%
“…Some intersex studies acknowledge the importance of emotion and online connections (e.g., Danon and Krämer 2017), but this is not their central focus. Finally, an experimental study offers useful insight into how viewers respond to online videos about social versus medical framings of intersex (Hegarty, Bogan-Carey and Smith 2019). This showed that student viewers preferred the video promoting the "social identity" intersex narrative over the medicalised narrative, and that the videos changed their beliefs about the harms and benefits of medicalisation.…”
Section: Healthcare and (Missing) Emotional Supportmentioning
confidence: 99%